Investigating Sustainable Entrepreneurship Practices in Small Food and Beverage Enterprises Across Urban Areas in England - William Edward Thompson; Charlotte Anne Kensington; Batarra Guterres (International Journal Business and Entrepreneurship, 2026)
This study explores sustainable entrepreneurship practices among small food and beverage enterprises in urban areas of England using a qualitative multiple case study approach. Drawing on Sustainable Entrepreneurial Orientation (SEO), the research investigates how entrepreneurs integrate environmental and social considerations into their business activities. Data were collected through semi-structured interviews, observations, and document analysis involving small business owners. The findings reveal that sustainability is primarily driven by personal values and ethical commitments rather than formal strategies. Entrepreneurs demonstrate proactive behavior through incremental innovations in resource management, particularly in waste reduction and efficiency practices. However, the study also identifies a persistent tension between financial constraints and sustainability goals, indicating that economic survival often influences decision-making. External factors such as consumer awareness and market demand further shape sustainability practices, creating both opportunities and limitations. Additionally, informal learning and local networks play a crucial role in facilitating sustainability adoption. This study contributes to the literature by providing a context-specific and process-oriented understanding of sustainable entrepreneurship in small enterprises. The findings offer practical implications for policymakers and practitioners in designing targeted support mechanisms for sustainable business development.